“Reduce, Reuse, Recycle”: Managing Library Print Collections - Acheson, Ann (Maine Policy Review, 2024)
Libraries strive to maintain print collections that are current and useful through both acquisition and removal of materials. Removal, often called “weeding,” is guided by factors that include accuracy, usage (circulation), physical condition, currency, relevance, and availability of materials elsewhere. Because of space limitations, smaller libraries and school libraries have more stringent weeding criteria. Ideally, weeded print materials are reused through various means if they are in good condition and not outdated or inaccurate. This article describes the various ways libraries handle their weeded books including book sales or bookstores, donations to local or national nonprofits, or online resellers. Materials that are not candidates for reuse may be sent for recycling, or, as a last resort, disposed of in the regular waste stream.